2014
DOI: 10.1007/s00220-014-1887-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Givental Formula with the Spectral Curve Topological Recursion Procedure

Abstract: We identify the Givental formula for the ancestor formal Gromov-Witten potential with a version of the topological recursion procedure for a collection of isolated local germs of the spectral curve. As an application we prove a conjecture of Norbury and Scott on the reconstruction of the stationary sector of the Gromov-Witten potential of CP 1 via a particular spectral curve.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
364
0
8

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 133 publications
(386 citation statements)
references
References 37 publications
3
364
0
8
Order By: Relevance
“…The Virasoro operators can be obtained from conjugation of local Virasoro operators by operators that reconstruct the partition function of the Gromov-Witten invariants from the partition function of Gromov-Witten invariants of a point. The work of [5] showed that topological recursion is equivalent to this reconstruction of Givental and Teleman. Hence one would expect that the global Virasoro constraints of Theorem 2 can be derived directly from the local Virasoro constraints.…”
Section: Define the Partition Function Which Stores Gromov-witten Invmentioning
confidence: 91%
See 3 more Smart Citations
“…The Virasoro operators can be obtained from conjugation of local Virasoro operators by operators that reconstruct the partition function of the Gromov-Witten invariants from the partition function of Gromov-Witten invariants of a point. The work of [5] showed that topological recursion is equivalent to this reconstruction of Givental and Teleman. Hence one would expect that the global Virasoro constraints of Theorem 2 can be derived directly from the local Virasoro constraints.…”
Section: Define the Partition Function Which Stores Gromov-witten Invmentioning
confidence: 91%
“…In Section 2 we recall the definition of descendant and ancestor Gromov-Witten invariants which are needed in the proof of Theorem 1. In Section 3 we review the topological recursion and its application to Gromov-Witten invariants of P 1 proven in [5], and derive a preliminary form of the global constraints from the local ones. Section 5 develops the regularised integral and its properties which is the main technical tool of this paper.…”
Section: Define the Partition Function Which Stores Gromov-witten Invmentioning
confidence: 99%
See 2 more Smart Citations
“…An other important development which aroses from matrix models around the same time is the topological recursion [16], which has grown into a polyvalent technique allowing to solve many problems of algebraic and enumerative geometry [17]. The relation between these two techniques has been shown in [19].…”
Section: Jhep08(2015)129mentioning
confidence: 99%